Upregulation of leucine-rich alpha-2 glycoprotein: A key regulator of inflammation and joint fibrosis in patients with severe knee osteoarthritis - Sarkar, Ashish; Chakraborty, Debolina; Kumar, Vijay; Malhotra, Rajesh; Biswas, Sagarika (Frontiers in Immunology, 2022)
Introduction: Osteoarthritis (OA) is a degenerative disease of joints mainly affecting at older age. Since the etiology behind the OA progression is not well understood, many associated consequences such as, synovial joint stiffness and its progression due to joint fibrosis is still poorly understood. Although many development has been achieved in the diagnosis and management of OA but, synovial fibrosis remains one of the major challenging consequences. The present study was therefore focused in understanding the mechanism of synovial fibrosis, which may further contribute to improve the symptomatic treatment, leading to the overall treatment outcome of OA patients. Methods: We have used the advanced proteomic technique such as Isobaric Tag for Relative and Absolute Quantitation and Sequential Window Acquisition of All Theoretical Mass Spectra techniques for identification of differentially expressed proteins in OA patient’s plasma samples. The in-silico study was carried out to evaluate the association of identified protein with their biological process related to fibrosis and remodeling of extracellular matrix. The most significantly upregulated protein was then validated by Western blot as well as Enzyme linked immunosorbent assay. The target protein was then further investigated for its role in inflammation and joint fibrosis by an in-vitro study model. Results: Leucine rich alpha-2 glycoprotein (LRG1) was found to be the most highly differentially expressed upregulated (9.4 fold) protein in OA patients’ plasma samples compared to healthy control. Knockdown of LRG1 followed by in-vitro studies revealed that LRG1 promotes secretion of extracellular matrix in synovial cells and actively playing role in wound healing and cell migration. The knockdown of LRG1 further confirmed the reduction of inflammatory and fibrosis related markers in primary cells. Conclusion: LRG1 was identified as the highly significant upregulated protein in OA patient’s plasma samples. It was found to be associated with increased fibrosis and cell migration, leading to enhance inflammation joint stiffness in OA pathogenesis.